1998
DOI: 10.3109/08880019809028791
|View full text |Cite
|
Sign up to set email alerts
|

All-Trans-Retinoic Acid (ATRA): Pediatric Acute Promyelocytic Leukemia

Abstract: Acute promyelocytic leukemia (APL) is a distinct subtype of acute myeloblastic leukemia (AML). In this report, we present the clinical features, management, and outcome of pediatric patients with APL treated with all-trans-retinoic acid (ATRA). Of 52 newly diagnosed cases of APL between February 1992 and December 1996, 15 were in the pediatric age group (younger than 15 years). Four patients were treated with ATRA alone and 11 were allocated to receive ATRA followed by chemotherapy. Eighty-six percent of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…According to Bapna et al [2] and Fenaux et al [10], the early death rate was significantly reduced by the treatment with ATRA.…”
Section: Discussionmentioning
confidence: 99%
“…According to Bapna et al [2] and Fenaux et al [10], the early death rate was significantly reduced by the treatment with ATRA.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the altogether lower incidence of AML in children compared to adults (AML only accounts for 15% of acute leukemia cases in children compared to 85% of acute leukemia cases in adults), APL is a comparatively rare event in children. Thus, despite the first report on the efficacy of ATRA in APL by Huang et al in 1988 [2] and apart from case reports, only a few studies have been reported supporting the benefits of ATRA in the treatment of childhood APL [29,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…[63][64][65][66][67][68] The results of contemporary treatment of children with APL also appear similar to those reported in adults. The CR rates for combination ATRA and anthracycline-based therapy have been reported to be 79% to 88% [68][69][70][71] and long-term EFS of 64% to 76%. [69][70][71][72] There are, however, some special considerations in treating children with APL.…”
Section: Prognostic Significance Of a Positive Molecular Test For Thementioning
confidence: 99%
“…The CR rates for combination ATRA and anthracycline-based therapy have been reported to be 79% to 88% [68][69][70][71] and long-term EFS of 64% to 76%. [69][70][71][72] There are, however, some special considerations in treating children with APL. The first special feature concerns the difficulty of some young patients to reliably swallow capsules.…”
Section: Prognostic Significance Of a Positive Molecular Test For Thementioning
confidence: 99%